Does wintering north or south of the Sahara correlate with timing and breeding performance in black-tailed godwits? - Kentie, R.; Marquez-Ferrando, R.; Figuerola, J.; Gangoso, L.; Hooijmeijer, C.E.W.; Loonstra, A.H.J.; Robin, F.; Sarasa, M.; Senner, N.; Valkema, H.; Verhoeven, M.A.; Piersma, T. (Ecology and Evolution, 2017)
Migrating long distances requires time and energy, and may interact with an individual’sperformance during breeding. These seasonal interactions in migratoryanimals are best described in populations with disjunct nonbreeding distributions.The black-tailedgodwit (Limosa limosa limosa), which breeds in agricultural grasslandsin Western Europe, has such a disjunct nonbreeding distribution: The majorityspend the nonbreeding season in West Africa, while a growing numberwinters north of the Sahara on the Iberian Peninsula. To test whether crossing theSahara has an effect on breeding season phenology and reproductive parameters,we examined differences in the timing of arrival, breeding habitat quality, laydate, egg volume, and daily nest survival among godwits (154 females and 157males), individually marked in a breeding area in the Netherlands for which winteringdestination was known on the basis of resightings. We also examinedwhether individual repeatability in arrival date differed between birds winteringnorth or south of the Sahara. Contrary to expectation, godwits wintering south ofthe Sahara arrived two days earlier and initiated their clutch six days earlier thangodwits wintering north of the Sahara. Arrival date was equally repeatable forboth groups, and egg volume larger in birds wintering north of the Sahara. Despitethese differences, we found no association between wintering location and thequality of breeding habitat or nest survival. This suggests that the crossing of animportant ecological barrier and doubling of the migration distance, twice a year,do not have clear negative reproductive consequences for some long-distancemigrants.